2018
DOI: 10.5223/pghn.2018.21.4.315
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Compliance and Efficacy of Isocaloric Oral Nutritional Supplementation Using 1.5 kcal/mL or 1 kcal/mL Sip Feeds in Mildly to Moderately Malnourished Indonesian Children: A Randomized Controlled Trial

Abstract: PurposeThis study set out to evaluate the compliance to, and efficacy of oral supplementation, using a 1.5 kcal/mL or 1 kcal/mL sip feed, in children with mild to moderate malnutrition.MethodsThis was a parallel, randomized, controlled open-label trial in children aged 3 to 6 years with a weight for height Z (WHZ) score <−1 and ≥−3, who were randomized to receive a total of 600 kcal/day from either a 1.5 kcal/mL or a 1.0 kcal/mL pediatric sip feed for 28 days. Assessments included daily study product intake, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…There were no significant differences between the groups with regard to the incidence rate of gastrointestinal symptoms, suggesting that the high-calorie formula was well tolerated among children with CP. It is in accordance with the earlier studies ( 37 , 38 ).…”
Section: Discussionsupporting
confidence: 94%
“…There were no significant differences between the groups with regard to the incidence rate of gastrointestinal symptoms, suggesting that the high-calorie formula was well tolerated among children with CP. It is in accordance with the earlier studies ( 37 , 38 ).…”
Section: Discussionsupporting
confidence: 94%
“…Overall, these findings support the safety and tolerance of the study ONS intervention (i.e., ONS + DC). The rates of GI tolerance AEs reported in the current study were comparable in type and incidence to those found in other studies investigating ONS in undernourished children ( 86 , 87 ).…”
Section: Discussionsupporting
confidence: 86%
“…This was distributed as follows: 600 kcal from solid food and 400 kcal prescribed through the ONS. The utilization of an ONS proves beneficial in enhancing the dietary intake and nutritional status of children facing challenges in meeting their nutritional needs solely through regular foods [ 2 , 21 , 34 , 35 ]. Our subjects’ calorie deficit was equivalent to 400 kcal, therefore it is reasonable to supply as much as 400 kcal/day of additional calorie intake through ONS intervention to meet their calorie requirements, with 100 kcal taken four times a day.…”
Section: Discussionmentioning
confidence: 99%